Financial performance of categorical banking sectors in Bangladesh (IIUC Business Review, 2022)
This study's objective is to assess the financial performance of the categorical banking sectors in Bangladesh from 2013 to 2017. The study used secondary sources of data that were collected from the Bangladesh Bank's annual reports. Through the use of the CAMEL test, an ANOVA, and an ordinary least squares model, this paper attempts to determine whether there are any appreciable differences in the capital adequacy, asset quality, management efficiency, earning ability, and liquidity among the four categories of banking sector in Bangladesh. The CAMEL test reveals that among the four types of banks, foreign commercial banks do the best. Among the four categories of banks, state-owned development financial institutions have performed the worst. When compared to one another, the four banking organizations' performance is found to be significantly different.IIUC Business Review Vol. 7-8, Dec. 2018-19 pp. 107-122